High-resolution facies analysis and regional correlation of the Upper Cretaceous Juana Lopez Member of the Mancos Shale, New Mexico - Wiercigroch, Monica (My University, 2018)
Fine-grained clastic sediments make up the gross lithology in interior basins of ancient epicontinental seas, such as the Cretaceous Western Interior Seaway. This study provides a high-resolution thin-bedded facies analysis and regional correlations to determine how the heterolithic units of the Juana Lopez Member of the Mancos Shale were transported and deposited in the San Juan Basin. Data for this study was obtained from outcrop observations in eleven measured sections, spanning a distance of 115 kilometers. Eleven facies are observed, four sequences and eleven parasequence sets are identified. A depositional model is determined through the high-resolution facies analysis, which suggests deposition on a proximal to distal mudbelt through multiple processes, including turbidity currents, hypopycnal plumes, wave enhanced sediment gravity flows (WESGFs), storm surges, tides and oceanic currents. Overall, the Juana Lopez is dominated by upward-shoaling parasequence sets, with an increasing number and thickness of sandstone dominated bedsets, suggesting regressive sedimentation with distal expressions of transgression found in two parasequence sets. The source of sediment is determined through 520 paleocurrent measurements and plaeogeographic data, and is determined to be transported by along-shelf currents, dominantly from proximal NE clastic wedges.
Keywords: Sedimentology; Stratigraphy; Mancos Shale; Heterolithic; Depositional Model; Facies Analysis